ببليوجرافيا في تاريخ عمان - فوزي, فاروق عمر (المورد, 1974)
The author treats briefly MSS and partial editions of Izkawī, Sirḥān b. Saʿīd: Kashf al-Ghumma al-jāmiʿ li-Akhbār al-Umma; Ibn Ruzayq: Tārīkh A’immat wa-Sādat ʿUmān; Sālimī, ʿAbdl. b. Ḥumayyid: Tuḥfat al-Aʿyān bi-Sīrat Ahl ʿUmān; [Ṣuḥārī], Abū ‘l-Mundhir Salma b. Muslim al- ʿAwtabī: Ansāb al-ʿArab. He mentions some other sources of Omani history, taken from Wilkinson 1972a, and gives a list of western secondary literature on Oman. This article is clearly the product of a first exploratory investigation into the history of Oman.
Place: العراق
Keywords: Bibliographie – Oman